Monitoring of NFAT-regulated gene expression in the peripheral blood of allograft recipients: a novel perspective toward individually optimized drug doses of cyclosporine A - Giese, Thomas; Zeier, Martin; Schemmer, Peter; Uhl, Waldemar; Schöls, Margarita; Dengler, Thomas; Büchler, Markus W.; Meuer, Stefan (Transplantation, 2004)
BACKGROUND: With the introduction of cyclosporine A (CsA), long-term allograft function has significantly improved. Problems related to limited therapeutic margins and CsA toxicity remain unsolved. Until now there have been no reliable, practical markers to measure the biologic activity of CsA in vivo. METHODS: Expression of NFAT (nuclear factor of activated T cells)-regulated genes (interleukin 2, interferon-gamma, and granulocyte-macrophage colony-stimulating factor) in phorbol myristate acetate/ionomycin-stimulated peripheral blood from healthy volunteers (n=34) and from stable renal (n=25), cardiac (n=26), and liver (n=14) transplant recipients receiving CsA therapy was measured by quantitative real-time reverse transcriptase-polymerase chain reaction before and 2 hr after drug intake. Gene expression and CsA plasma levels were correlated. RESULTS: Two hours after oral CsA ingestion, the mean suppression of induced interleukin 2, interferon-gamma, and granulocyte-macrophage colony-stimulating factor gene expression was 85%. The individual decline of NFAT-regulated gene expression and the total drug exposure at this time point were closely related. Six hours after oral CsA uptake, gene expression levels reached predose values and subsequently increased further in some patients (rebound effect). CONCLUSION: Quantitative measurement of the inhibition of NFAT-regulated gene expression 2 hr after CsA intake represents a novel approach to assess the biologic effectiveness of CsA therapy and has the potential to enable individualized immunosuppressive regimens.
Gesehen am 16.06.2021